Agribusiness succession and agricultural sustainability: What could hamper succession - TAN, Wee Liang (Institutional Knowledge at Singapore Management University, 2020)
This paper examines the relationship between agribusiness succession and agribusinesses sustainability. Most agribusinesses are family run. Hence, the paper argues these businesses are no different from family businesses. In order for them to continue as agribusinesses, there needs to be succession in the family over the business. Should the subsequent generations have no interest in agribusiness, the likelihood that the ownership of the business could be changed or decline in the agribusiness output. Alternatively, there could be family disputes and conflicts over the right to manage the farm, which affect the agribusinesses.